Chronic methylmercury exposure causes spinal cord impairment: proteomic modulation and oxidative stress - Eiró, Luciana Guimarães (2020)
Methylmercury (MeHg) is considered by the World Health Organization (WHO) as one of the chemicals of greatest public health concern. Although central nervous system (CNS) is the main target organ, the effects over the spinal cord are not well understood, especially in chronic exposure at similar doses to those faced by humans. This study aimed to investigate possible changes on global proteomic profile and oxidative biochemistry status of rats spinal cord, related to the maintenance and balance of the organism functioning, mimicking a human daily exposure by diet (chronic and with relatively low levels). For this, 28 adults male Wistar rats were divided into two groups: MeHg group, which was intoxicated by intragastric gavage with MeHg at a dose of 0.04 mg/kg/day for 60 days, and control group, that received only vehicle. After the exposure period, the spinal cords were collected for evaluation of total mercury levels, proteomic profile, with further bioinformatic overrepresentation analysis (ORA), and oxidative biochemistry, by analyzing the antioxidant capacity against peroxyl radicals (ACAP), lipid peroxidation (LPO), nitrite levels, measurement of Trolox Equivalent Antioxidant Capacity (TEAC) and Reduced Glutathione (GSH). The MeHg exposure increased total mercury levels in spinal cord parenchyma, which increased lipid peroxidation and nitrite levels, and reduced antioxidant status. The proteomic analysis showed several proteins related to biological processes, cellular components and molecular functions. Moreover, according to the ORA analysis, the proteins are involved in processes such as mitochondrial activity, stress response, cytoskeleton and apoptosis. Therefore, we concluded that exposure to low doses of MeHg can activate the oxidative stress pathway and thus, modulate the status of regulation of several important proteins.